Experimental investigation of capillary threshold pressure in shale - Arain, A.H. (Science and Engineering Research Support Society, 2020)
The decline in oil price has made operators ever-cautious for improving efficiency to reduce drilling problems and costs. The proper selection of drilling fluid is the key to the success of drilling operation. The major problems encountered during drilling are related to wellbore instability and shales are considered to be the main cause. Shalesare the most problematic and challenging formations encounter during drilling. The unfavourable interaction between the shale and the water-based mud is considered to be the primary cause of shale instability. The fluid invasion increases the pore pressure and reduces the shale strength by altering the stress state of shale. Whereas, hydration of shale can cause the development of swelling stress and results in wellbore instability. Oil-based mud can be used instead of water-based mud to overcome the problem caused by the interaction of shale and water-based mud. The interaction between the oil-based muds with shale is much simpler than that of water-based mud and shale. The low permeable water-wet shales generate high capillary forces which prevent the fluid flow into the shale even at significant overbalance pressures. However, if the wellbore pressure would be adequately high enough, it may overcome the capillary forces and invade the formation and cause wellbore instability. Therefore, during the drilling process, it must be known that how much the wellbore pressure should be to avoid invasion in shale. The main objective of this research study is to determine the capillary threshold pressure in shale. A laboratory testing setup and procedure was established to perform the capillary threshold pressuretests. These tests were performed at overburden pressure and room temperature conditions. Two different shale samples were selected for the study from Pierre shale of marine origin. The Standard approach has been utilized for the measurement, which consists of a consolidation phase and capillary threshold pressure phase. The standard approach was selected due to its high accuracy for the measurements of capillary threshold pressure. The experimental result shows that the capillary threshold pressure depends on the interfacial tension between the oil and water phases, pore throat radius and shale permeability. Â© 2019 SERSC.